2021
DOI: 10.1111/nmo.14199
|View full text |Cite
|
Sign up to set email alerts
|

Gastric electrical stimulation improves symptoms and need for supplemental nutrition in children with severe nausea and vomiting: A ten‐year experience

Abstract: Background Gastric electrical stimulation (GES) is a promising therapy for children with severe nausea and vomiting, but information on long‐term outcomes is limited. We sought to evaluate the long‐term efficacy and safety of GES and to describe patient benefit and satisfaction. Methods Using a prospective registry, we identified patients aged <21 years treated with GES at our institution between 2009 and 2019. Encounters were selected at baseline prior to GES and at follow‐up at 1 month, 12 months, and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Moreover, in the current study, burps, acid reflux, regurgitation, and a bloated feeling were more prevalent in children with nausea, suggesting that an altered gastric motility indeed plays a role in the pathophysiology of nausea. At the same time, gastric electrical stimulation can improve symptoms in children with severe nausea 27,28 . Since the vagal nerve influences gastric emptying, dysfunction of the parasympathetic nervous system it likely plays a role in the pathogenesis of nausea 17,29,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the current study, burps, acid reflux, regurgitation, and a bloated feeling were more prevalent in children with nausea, suggesting that an altered gastric motility indeed plays a role in the pathophysiology of nausea. At the same time, gastric electrical stimulation can improve symptoms in children with severe nausea 27,28 . Since the vagal nerve influences gastric emptying, dysfunction of the parasympathetic nervous system it likely plays a role in the pathogenesis of nausea 17,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, gastric electrical stimulation can improve symptoms in children with severe nausea. 27,28 Since the vagal nerve influences gastric emptying, dysfunction of the parasympathetic nervous system it likely plays a role in the pathogenesis of nausea. 17,29,30 Physiological testing in pediatric patients with chronic unexplained nausea has indeed shown a decreased heart rate variability, suggesting reduced parasympathetic tone and underlying dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic abdominal pain is caused by visceral hypersensitivity, while chronic nausea is likely the result of a change in gut motility. [37][38][39] It is known, however, that hypnosis can affect both hypersensitivity and motility. Lowén et al 16 showed, using a barostat for rectal distensions and functional magnetic resonance imaging, that abnormal processing and enhanced perception of visceral stimuli in IBS can be normalized after hypnotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabinoids have been studied extensively for prevention and treatment of nausea and vomiting associated with chemotherapy (42), but their chronic use may also cause dyspeptic symptoms including nausea and protracted emesis (43). Finally, there is increasing evidence that neuromodulation with implantation of a gastric pacemaker improves drug-refractory nausea, regardless of the effect of this device on gastric emptying (44). The mechanism by which such improvement is triggered is not yet fully clarified and is likely to include modulation of central, autonomic, and enteric pathways.…”
Section: Treatmentmentioning
confidence: 99%